POSSIBILITIES OF STUDYING OF NANOOBJECTS IN POROUS SILICON AND WAFERS OF SILICON IRRADIATED BY PROTONS BY METHOD OF POSITRON ANNIHILATION SPECTROSCOPY - Grafutin, V.I.; Ilyukhina, O.V.; Myasishcheva, G.G.; Prokopiev, E.P.; Timoshenkov, S.P.; Funtikov, Yu.V. (Recent Contributions to Physics, 2018)
It is shown, that one of effective modern methods of definition of the nanodefect sizes (vacancies, vacansion clasters), free volumes of porous, cavities, emptiness in nanomaterials and porous systems is the method of positron annihilation spectroscopy (PAS). Examples of definition of the sizes and concentration of porous and free volumes in porous silicon, silicon and the monocrystals of quartz irradiated by protons are resulted.